FOREIGN EXPERIENCES AND THEIR USE IN DEVELOPING THE SERVICE SECTOR IN RURAL AREAS IN UZBEKISTAN (European Journal of Economics, Finance and Business Development, 2025)
This article explores the potential of foreign experiences in shaping the development of the service sector in rural areas of Uzbekistan. It analyzes successful models from various countries and examines their applicability to Uzbekistan's unique socio-economic landscape. The research highlights the challenges faced by the current service sector in rural regions and identifies key areas where foreign practices can enhance service delivery, improve access, and promote economic growth. By integrating best practices from abroad, Uzbekistan can effectively address the service gaps in its rural areas and drive sustainable development.